Shi'ite Lebanon: Transnational Religion and the Making of National Identities - Shaery-Eisenlohr, Roschanack (History and Society of the Modern Middle East, 2008)
Roschanack Shaery-Eisenlohr proposes a new framework for understanding Shi'ite politics in Lebanon and reconsiders not only the politics of Shi'ites' established leadership but also the institutional and popular activities of identity production. Shaery-Eisenlohr traces current Shi'ite politics of piety and authenticity to the coexistence formula in Lebanon and argues that engaging in the discourses of piety and coexistence is a precondition to cultural citizenship in Lebanon. She demonstrates that debates over the nature of Christianity and Islam and Christian-Muslim dialogue are in fact intertwined with power struggles at the state level.Since the 1970s, debates in the transnational Shi'ite world have gradually linked Shi'ite piety with the support of the Palestinian cause. Iran's religious elite has backed this piety project in multiple ways, but in doing so it has assisted in the creation of a variety of Lebanese Shi'ite nationalisms with competing claims to religious and national authenticity. Shaery-Eisenlohr argues that these ties to Iran have in fact strengthened the position of Lebanese Shi'ites by providing economic, military, and ideological support for Hizbullah, as well as compelling Lebanese Shi'ites to foreground the Lebanese components of their identity more forcefully than ever before. Shaery-Eisenlohr challenges the belief that Shi'ite identity politics only serve to undermine the Lebanese national project. She also makes clear that the expression of Lebanese Shi'ite identity is a nationalist expression and an unintended result of Iranian efforts to influence the politics of Lebanon.